Stanley Fish's Case for Speech Regulation: A Critique - Ryan, Phil (Canadian Journal of Higher Education, 2001)
This article critiques Stanley Fish's argument for speech regulation. Fish errs in reducing free speech to a mere means, viewing free speech as a "conceptual impossibility," and making the limited speech rights of the modern workplace a standard for assessing speech rights in general.